The end of the road - Bodett, Tom. (New York : W. Morrow, 1989)
Radio personality shares short witty pieces on small-town life, family life, and everyday experience, all from the perspective of an ex-logger and resident of Homer, Alaska.
Big bazaar -- Ed again -- Tamara and the cat -- Missing youth -- Tamara and Ed -- Tamara and Ed go bowling -- Jenuwine McDoogan -- Storbock fire -- Lucky break -- Norman's Thanksgiving -- Every little boy's dream -- Doug's stuff -- Ruby's video roundup -- Town tree -- Yet another new year -- Night in the pass -- Tamara's brother -- New guy -- Bud's birthday -- Emmitt Frank -- Clara's coffee cup -- Norman's secret -- Doug's opening -- Expert -- Officer and Tamara -- Best sauna story so far.
6 7 13 19 21 33
Keywords: American wit and humor -- Alaska -- Fiction; Alaska -- Social life and customs -- Fiction; Alaska -- Fiction; Humorous stories; Short stories